Transient Common Peroneal and Tibial Nerve Palsy Following Knee Arthroscopy for the Treatment of Discoid Lateral Meniscus - Bernardi, Gabriele; Tudisco, Cosimo (Joints, 2017)
The number of knee arthroscopies has increased rapidly since the 1980s and are among the most common orthopedic procedures today. It is generally considered a minimally invasive surgery with relatively low morbidity, but it is not without risk of complications. We report the case of a 14-year-old boy who developed a lesion of common peroneal nerve and tibial nerve after knee arthroscopy for a torn discoid lateral meniscus, which was confirmed by electromyogram study.
Keywords: complications; knee arthroscopy; tibial nerve; common peroneal nerve; discoid meniscus